2021
DOI: 10.1186/s12947-021-00260-3
|View full text |Cite
|
Sign up to set email alerts
|

Global and regional right ventricular mechanics in repaired tetralogy of Fallot with chronic severe pulmonary regurgitation: a three-dimensional echocardiography study

Abstract: Background Data about the right ventricular (RV) mechanics adaptation to volume overload in patients with repaired tetralogy of Fallot (rToF) are limited. Accordingly, we sought to assess the mechanics of the functional remodeling occurring in the RV of rToF with severe pulmonary regurgitation. Methods We used three-dimensional transthoracic echocardiography (3DTE) to obtain RV data sets from 33 rToF patients and 30 age- and sex- matched controls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
(37 reference statements)
1
7
0
Order By: Relevance
“…Compatible with our results, previous studies on the biventricular function in rTOF patients using strain derived from MRI feature‐tracking 32 or echocardiology 33,34 have shown reduced myocardial longitudinal function. The rTOF group presented a loss of RV KE z and %KE z in both systole and diastole, which may contribute to impairment of the RVEF.…”
Section: Discussionsupporting
confidence: 91%
“…Compatible with our results, previous studies on the biventricular function in rTOF patients using strain derived from MRI feature‐tracking 32 or echocardiology 33,34 have shown reduced myocardial longitudinal function. The rTOF group presented a loss of RV KE z and %KE z in both systole and diastole, which may contribute to impairment of the RVEF.…”
Section: Discussionsupporting
confidence: 91%
“…This in turn has led to a new generation of adolescents who may be prone to the development of heart failure due to residual lesions after correction or palliation of their cardiac defect ( 3 , 4 ). The most prevalent of residual lesions after surgical correction is pulmonary regurgitation after correction for tetralogy of Fallot (TOF), leading to right ventricular (RV) volume overload (VO) ( 5 , 6 ). Long-standing RV VO will induce RV dysfunction, and thus RV VO could serve as a prognostic index in the TOF population ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…CMR is ideal for accurate quantification of RV volumes and EF; however, 3D echocardiography might help with regular follow-up evaluation and longitudinal RV measurements in this patient population [10]. Furthermore, 3D strain measurements in repaired TOF population revealed that the relative contribution of the longitudinal component to global RVEF was more prominent than either the radial or the anteroposterior shortening [119]. Two-dimensional echocardiography-derived vena contracta diameter, PISA-derived EROA, and 3D-echocardiography-derived vena contracta area can be used to quantify the recently proposed severe, massive, and torrential grades of TR, respectively [12,110,111].…”
Section: Rv Volume Overloadmentioning
confidence: 99%